Population dynamics of the mud crab Panopeus austrobesus Williams, 1983 (Brachyura: Panopeidae) associated with a mussel farm at the southeastern Brazilian coast - Camargo, Flavio De Vasconcelos; Alves, Douglas Fernandes Rodrigues; Lima, Daniel José Marcondes; Cobo, Valter José (Sociedade Brasileira de Carcinologia, 2017)
Abstract Mussel farms are one of the most important modalities of aquaculture and constitute almost 80% of the total bivalve production in Brazil, representing about 5% of the national production. Brachyuran crabs are common inhabitants of these environments and represent an important link in coastal marine food chains. The aim of this investigation is to describe the population structure of Panopeus austrobesus Williams, 1983 in a Perna perna (Linnaeus, 1758) farm located at the southeastern Brazilian coast. The samplings were carried out in the northeastern coast of São Paulo State. From May 2002 to April 2003, one mussel net was recovered monthly, and all individuals of P. austrobesus were collected. Population size-frequency analysis indicated a unimodal and non-normal distribution. Males were significantly larger than females, and the overall sex ratio significantly skewed from 1:1, female-biased. Recruitment occurred during the entire period, and ovigerous females were found in 11 months. The onset of sexual maturity was estimated around 5 mm cephalothorax width. Mussel farms represent an anthropogenic intervention in the sea landscape, causing environmental changes. However, these structures must allow species introduction, increasing their ecological and geographical distribution, and provide available space and food to establish new populations. This is particularly important for species with small populations, such as P. austrobesus. The results of this study attest the environmental counterpart role of the mussel farms. Once they can support populations, they may also help to reintroduce them into the area and could therefore be used in a consortium generating economic profits and acting as bioremediation tool, assuring the maintenance of the genetic patrimony.
Keywords: Brown mussel; conservation; mariculture; Perna perna; Ubatuba